Didactic positions on the scientific method and development of research skills in university students - Zacarías Ventura, Héctor Raúl (2021)
Objective. To show that the didactic positions with quantitative vs. conceptualist-epistemological approach of the teacher on the scientific method influence the development of research skills in the university student. Methods. It consisted of pure / basic, observational, analytical, prospective and transversal research. The level of research was explanatory, assessing the causality of one variable over the other. The population consisted of 570 students from the last semester of studies of Universidad de Huánuco, enrolled in the academic cycle 2020-I. The sample consisted of 215 students, chosen by means of a stratified random sample. A documentary measurement instrument adapted from Jaik and Ortega’s scale of assessment of investigative competencies (2017) was used. Results. The results confirm that the didactic posture of the teacher on the scientific method influences the research skills of the university student, with a probability of error of 3.2%. Conclusions. It is concluded that the didactic posture of the teacher on the scientific method effectively influences the development of research skills of the university student.